2003
DOI: 10.1051/rnd:2004003
|View full text |Cite
|
Sign up to set email alerts
|

Location of myostatin expression during bovine myogenesis in vivo and in vitro

Abstract: -Mutations in the myostatin gene lead to double-muscling in cattle indicating that it is a negative regulator of the total number of muscle fibres. Myostatin expression was analysed by RT-PCR in three developing bovine muscles. It decreased during differentiation in Semitendinosus and Biceps femoris, and increased in the late differentiating Masseter during gestation. A combination of in situ hybridisation and immuno-histochemical detection of myosin heavy chains (MHC) allowed us to locate the expression in my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
4
15
0
Order By: Relevance
“…The current data demonstrated that myocyte proliferation was decreased with increasing expression of myostatin by aging. Our findings support previous reports indicating that aging-induced increase in myostatin expression caused the suppression of myocyte proliferation [30]. …”
Section: Discussionsupporting
confidence: 93%
“…The current data demonstrated that myocyte proliferation was decreased with increasing expression of myostatin by aging. Our findings support previous reports indicating that aging-induced increase in myostatin expression caused the suppression of myocyte proliferation [30]. …”
Section: Discussionsupporting
confidence: 93%
“…In fact Liu et al [20] have shown that GH had an inhibitory effect on myostatin expression. In our model, we showed that GHR mRNA level increased from 130 dpc mainly in double-muscled animals and, in another study, that myostatin mRNA expression (which was very high at 110 dpc) decreased considerably during the second third of gestation both in normal and double-muscled animals [22]. The increase in GHR mRNA was perhaps due to an increase in foetal GH or of the GH-like level.…”
Section: Discussionsupporting
confidence: 59%
“…One of the objectives of the present study was to investigate the ontogeny of GHR mRNA and to compare it to that of IGF-II [8] and myostatin [22] mRNA previously described in the same samples in our laboratory. In addition, in order to better understand the regulation of the differentiation of muscle fibres, we chose an hypertrophied muscle in double-muscled animals, the semitendinosus (ST) muscle.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of DM muscles appear during foetal development (Picard et al, 1995;Deveaux et al, 2001). MSTN expression is detected from 16 days in bovine embryos (Kambadur et al, 1997) and is regulated throughout gestation (Deveaux et al, 2003). An increase in the total number of fibres has been observed in DM muscles during the foetal period (Swatland and Kieffer, 1974;GagniĂš re et al, 2000).…”
Section: Introductionmentioning
confidence: 99%